Association of inflammatory index with the severity of disease in patients with acute myocarditis: A retrospective observational study - Wang, Shipeng; Xu, Hanchi; Guo, Zhen; Tian, Yulin; Guo, Xia; Chu, Haoxuan; Wang, Yushi (Frontiers in Endocrinology, 2025)
PurposeThis research aimed to investigate the association between neutrophil-percentage-to-albumin ratio (NPAR), systemic immune-inflammation index (SII), systemic inflammation response index (SIRI), and aggregate index of systemic inflammation (AISI) with disease severity in patients diagnosed with acute myocarditis.MethodsA total of 185 patients were diagnosed with acute myocarditis at the First Hospital of Jilin University between 2018 and 2024. The related values of NPAR, SII, SIRI, and AISI were computed based on the pertinent blood indices that were acquired within 12 hours of admission. The best cut-off values for NPAR, SII, SIRI, and AISI, as well as their associated sensitivity and specificity, were determined using ROC curve analysis in order to assess their predictive usefulness for poor prognosis upon admission.ResultsPatients with fulminant myocarditis exhibited significantly higher NPAR, SII, SIRI, and AISI values compared to those with mild myocarditis. Spearman correlation analysis revealed significant associations between these inflammatory indices and NYHA scores at admission (r = 0.370, 0.296, 0.284, and 0.246, respectively; P < 0.01). Multivariate logistic regression analysis identified high NPAR (OR: 5.44 95%, CI:1.81 ~ 16.36, P=0.003), SII (OR: 1.01 95%CI:1.01 ~ 1.01, P=0.010), SIRI (OR: 1.21, 95%CI:1.06 ~ 1.37, P=0.005), and AISI (OR: 1.01 95%CI:1.01 ~ 1.01, P=0.007) values as independent risk factors for myocarditis severity.ConclusionsOur study demonstrated that inflammatory biomarkers - NPAR, SII, SIRI, and AISI - show associations with the severity of acute myocarditis.